Preparation method for electron beam selective melting printing porous thin-wall structure

Through electron beam selection melting printing technology and multi-step processing method, a porous thin-wall titanium alloy structure with excellent mesoporous characteristics and high mechanical properties was prepared, which solved the formingability, porosity and mechanical properties in the preparation of titanium alloys in the prior art. The issue of balance has achieved widespread application in the field of biomedical medicine.

CN119457117AActive Publication Date: 2025-02-18UNIV OF SCI & TECH BEIJING +1

Patent Information

Application Number
CN202411454237.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-02-18
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The prior art is difficult to achieve a balance between formability, porosity and mechanical properties in the preparation of titanium alloys with complex geometric shapes and internal micron-scale porous structures, especially under tensile loads, and biocompatible and The applicability of pore structure is limited.

Method used

Using electron beam selection melting printing technology, a porous thin-wall model was designed through three-dimensional modeling software, and a narrower melt pool was printed using dot melting and jump strategies, combining stress removal annealing, thermal isostatic pressure, acid solution treatment and Treatment of zinc hydroxide aqueous solution to prepare a porous thin-walled structure with excellent mesoporous characteristics and high mechanical properties.

Benefits of technology

The porous thin-walled structure has extremely small thickness, high porosity and excellent mechanical properties, and has improved biocompatibility through treatment. It is suitable for bone repair in complex shapes and meets high mechanical properties requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119457117A_ABST
    Figure CN119457117A_ABST
Patent Text Reader

Abstract

The invention provides an electron beam selective melting printing porous thin-wall structure preparation method, and relates to the technical field of medical skeleton repair. The preparation method of the electron beam selective melting printing porous thin-wall structure comprises the steps of titanium alloy powder selection, software modeling, printing parameter setting, scanning line selection, destressing annealing heat treatment, hot isostatic pressing, acid solution treatment and zinc hydroxide aqueous solution low-temperature treatment. According to the preparation method disclosed by the invention, the formability, porosity, mechanical property, biocompatibility and other properties of the prepared porous thin-wall structure can be synergistically improved; the thickness, porosity, strength and other properties can be customized, the resource utilization rate is high, the process is short, the efficiency is high, the application range of the product in the biomedical aspect is wide, and industrial large-scale production and popularization are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of medical bone repair, and in particular to a method for preparing porous thin-walled structures using electron beam selective melting printing. The resulting porous thin-walled structures are not only extremely thin but also possess excellent mesoporous properties and superior mechanical properties. These structures can be bent and coated onto bones of various shapes. Background Art

[0002] Titanium alloys are widely used in the biomedical field due to their high specific strength, corrosion resistance, and good biocompatibility. Because cells need to adhere to the surface of implants for growth, porous structures with high specific surface area have been introduced into the research of biomedical titanium alloys. Traditional titanium alloy preparation methods are limited to producing samples with regular shapes such as cylinders. However, human bones and joints have more complex geometries and internal structures, which are difficult to achieve with traditional preparation methods.

[0003] Additive manufacturing, a method that slices and prints 3D CAD models layer by layer, enables the precise printing of complex models in three dimensions. This process enables precise control of the complex geometries and micron-scale porous structures of biological structures, allowing for the free design of pore size and structure.

[0004] At present, people have conducted extensive research on the lattice structure of different materials, and have conducted in-depth research on their formation, microstructure, mechanical properties and biological properties. However, in the current research on lattices, the mechanical properties are mainly focused on compression properties. In terms of biomaterials, the loads borne by human bones include compressive loads and tensile loads, and they are more susceptible to damage and destruction under tensile loads. There are few studies in the prior art on the relationship between the effect of tensile loads on destruction and porous structures, and the mechanism is not clear. In particular, although the increase in porosity in porous structures is conducive to the growth of human tissue after implantation, it also increases the difficulty of preparation and reduces the mechanical properties.

[0005] Therefore, how to strike a balance between formability, porosity and mechanical properties in the preparation of titanium alloys with complex geometries and internal micron-scale porous structures is an urgent problem to be solved.

[0006] For example, Chinese patent CN117548691A discloses a method for additive manufacturing of porous materials. This method controls the molten pool overlap rate to above 80%, so that the elements inside each molten pool are fully evaporated to form pores, thereby obtaining a porous material. By artificially creating pore defects during the printing process, the preparation of bulk porous materials is achieved. However, the printing defects introduced by this method are randomly distributed, and there are no channels connecting the pores, which is not suitable for application in biomaterials.

[0007] Chinese patent CN118022054A discloses a customizable bone defect repair material and its preparation method. This method uses collagen as a framework material and decalcified bone matrix with good osteogenesis as a hard material to enhance the mechanical support of the material. Although this method is relatively good at repairing bone defects, it has defects in mechanical properties and is difficult to meet scenarios with high mechanical performance requirements, such as bone support.

[0008] Chinese patent CN117883222A discloses a combined femoral stem for hip joint prosthesis and a preparation method thereof. In this method, the femoral stem is made of forged titanium alloy plate and / or forged cobalt-chromium alloy plate as the first raw material and processed; the porous part is made of forged titanium alloy powder and / or forged cobalt-chromium alloy powder as the second raw material and is made into an integral part by 3D printing; obviously, this method is difficult to manufacture and has complex steps. It requires the preparation of a targeted prosthesis based on the patient's bone morphology, and the porous structure on both sides has large pores and a low surface area, making it difficult for cells to attach and grow.

[0009] Chinese patent CN104645419A discloses a method for preparing a porous titanium alloy femoral head support rod with a bionic trabecular bone structure. The titanium alloy powder selected is Ti6Al4V or Ti2448 spherical powder. After printing, it needs to be treated with an acid solution to increase the surface roughness. Then, PLGA nanospheres, BMP-2 and VEGF complexes are constructed on its surface to facilitate bone tissue ingrowth; biocompatibility is obviously improved, but the mechanism of tensile strength and flexural strength on material damage, as well as the relationship between the porous structure and porosity are still unknown.

[0010] Chinese patent CN112168431A discloses a method for preparing a functional bionic porous titanium alloy femoral head support rod. The method first prints a porous titanium alloy femoral head support rod, and then prepares a high-purity magnesium coating on its inner and outer surfaces. The prepared structure is not a porous thin-walled structure, and its shape, mechanical properties and specific surface area are not suitable for porous thin-walled structures. Biocompatibility is achieved through the magnesium coating. Summary of the Invention

[0011] In order to solve the technical problems that the existing technology of printing biomaterial titanium alloy can only prepare regular-shaped samples such as bulk porous materials, cylinders, femoral stems, biomimetic trabecular femoral head support rods, and the improvement of biocompatibility is achieved through coatings, biological factor complexes, etc.; therefore, the embodiment of the present invention provides a method for preparing porous thin-walled structures by electron beam selective melting printing, which can coordinate the formability, porosity, mechanical properties and biocompatibility of porous thin-walled structures. The technical solution is as follows:

[0012] A method for preparing a porous thin-walled structure by electron beam selective melting printing, the method comprising the following steps:

[0013] S1. Raw material selection: selecting titanium alloy rotating electrode powder according to the performance requirements of the porous thin-walled structure to be prepared, to obtain raw titanium alloy powder or raw titanium aluminum alloy powder;

[0014] S2. Modeling: Using 3D modeling software to model the porous thin-walled structure according to its dimensions, a porous thin-walled model is obtained, and corresponding parameters are set for the molten pool width and the interval between the point-shaped molten pools in the porous thin-walled model;

[0015] S3. Printing parameter setting: The printing parameters need to be set within the density parameter range of the porous thin-walled structure to be prepared, so as to print a molten pool with a narrow width and high overlap efficiency;

[0016] S4, scan line selection and printing: When selecting the scan line, use the point melting and jump strategy; after the parameters are set and the scan line is selected, start printing the porous thin-walled structure;

[0017] S5. Cutting and stress relief annealing heat treatment: After printing, the porous thin-walled sample is cut from the base plate using a wire cutting method, sealed with a quartz tube and filled with argon gas, and then placed in a muffle furnace for stress relief annealing heat treatment, heating and cooling with the furnace;

[0018] S6. Hot isostatic pressing: The annealed sample is subjected to hot isostatic pressing to obtain a porous thin-walled sample with enhanced powder adsorption;

[0019] S7, acid solution treatment: treating the porous thin-walled sample with enhanced powder adsorption with an acid solution, and then performing ultrasonic cleaning to obtain a porous thin-walled sample with increased surface roughness;

[0020] S8. Treatment with zinc hydroxide aqueous solution: The porous thin-walled sample with increased surface roughness is treated with zinc hydroxide aqueous solution at low temperature, then treated at high temperature, and finally ultrasonically cleaned and dried to obtain a porous thin-walled final product with high biocompatibility and fine zinc titanate grown on the surface.

[0021] Optionally, the particle size of the raw titanium alloy powder in S1 is 50-200 μm, and the types of titanium alloys include α-type titanium alloys and α+β dual-phase titanium alloys; the particle size of the raw titanium aluminum alloy powder is 50-150 μm, and the types of titanium aluminum alloys include 4822 alloy.

[0022] Optionally, the 3D modeling software in S2 includes Solidworks or UG, the size range of the porous thin-walled model is 300-900 μm, the porous part is obtained by the interval of the point-shaped molten pool, the molten pool width in the model is 150-300 μm, and the actual molten pool width is determined by the printing parameters and needs to be fed back and corrected based on the previous printing parameter range of the porous thin-walled structure to be prepared.

[0023] Optionally, in S3, when the porous thin-walled structure component to be prepared is TC4, the printing parameters are set to a scanning speed of 1.5-3.0 m / s, a defocus value of 50, and a current of 60-120 mA; when the porous thin-walled structure component to be prepared is TA15, the printing parameters are set to a scanning speed of 1.0-2.5 m / s, a defocus value of 30, and a current of 70-130 mA; when the porous thin-walled structure component to be prepared is TC11, the printing parameters are set to a scanning speed of 1.0-2.5 m / s, a defocus value of 50, and a current of 80-150 mA; when the porous thin-walled structure component to be prepared is TA17, the printing parameters are set to a scanning speed of 1.2-2.8 m / s, a defocus value of 40, and a current of 90-160 mA.

[0024] Optionally, the stress relief annealing heat treatment in S5 is performed at a heating temperature of 650-750°C, a heating rate of 5-10°C / min, a holding time of 1-2h, and a cooling rate of 10-20°C / min.

[0025] Optionally, the heating temperature of the hot isostatic pressing treatment in S6 is 850-1000° C., the gas pressure is 100-150 MPa, the gas medium is argon, and the holding time is 2-4 hours.

[0026] Optionally, the acid solution for the acid solution treatment in S7 is HF:HNO3:H2O in a ratio of 1:1:2, and the treatment time is 10-30 min; the frequency of ultrasonic cleaning is 20-40 Hz, and the power is 50-300 W; the thickness of the porous thin-walled sample with increased surface roughness is 100-500 μm, the porosity is 10-30%, the pore diameter is 50-200 μm, the surface roughness is Ra1-10 μm, the surface area is 200-1000 m² / m³, and the tensile strength is 100-400 MPa.

[0027] Optionally, the low-temperature treatment of the zinc hydroxide aqueous solution in S8 is to place the porous thin-walled sample with increased surface roughness into a 0.1-0.5M zinc hydroxide aqueous solution for low-temperature treatment at 20-30°C for 1-2 hours; the high-temperature treatment is to subject the porous thin-walled sample with increased surface roughness after the low-temperature treatment with the zinc hydroxide aqueous solution to a high-temperature treatment at 80-90°C for 5-7 hours; the fine zinc titanate is in the form of flaky or columnar crystals with an average size of 1-10 μm.

[0028] Technical principle of the present invention:

[0029] The present invention uses 3D software to draw a porous thin-wall model, imports the model into slicing software to generate a printing model, uses printing parameters to generate a point-shaped narrow molten pool, performs stress relief annealing after printing, and performs hot isostatic pressing to further increase the bonding force between powders.

[0030] The present invention uses acid solution treatment to increase the surface roughness and generate dendritic nano-scale titanium alloy on the surface, and then uses zinc hydroxide solution to perform multi-step hydrothermal treatment to generate finer zinc titanate on the titanium alloy surface, further enhancing the contact area and biocompatibility.

[0031] The porous thin-walled structure prepared by the present invention not only has an extremely small thickness, but also has excellent mesoporous characteristics and relatively good mechanical properties.

[0032] Compared with the prior art, the above technical solution has at least the following beneficial effects:

[0033] The above scheme, the present invention proposes a method for preparing porous thin-walled structures by electron beam selective melting printing, which can solve the technical problems that in the existing technology, printing biomaterial titanium alloys can generally only prepare regular-shaped samples such as bulk porous materials, cylinders, femoral stems, bionic trabecular structure femoral head support rods, and the improvement of biocompatibility is through coatings, biological factor complexes, etc.

[0034] The porous thin-walled structure prepared by the present invention is extremely thin, with a minimum thickness of 300-400 μm, which is much lower than the porous structures in other existing technologies. It can provide high strength and plasticity while maintaining porosity, making it more widely applicable in biomedicine.

[0035] The porous thin-walled structure prepared by the present invention has excellent mechanical properties, with a porosity of up to 30%, a pore diameter of up to 200μm, a surface roughness of up to Ra1, a surface area of ​​up to 1000m² / m³, and a tensile strength of up to 400MPa. It can meet higher mechanical performance requirements as a bone fixation and repair material.

[0036] The porosity of the porous thin-walled structure prepared by the present invention can be controlled in the range of 10-30%, and different porosities can be controlled by adjusting the model and printing parameters.

[0037] The porous thin-wall structure prepared by the present invention can improve the surface roughness by at least 50% on the original basis through acid solution treatment and zinc hydroxide solution treatment.

[0038] The present invention can be coated on bones of various shapes by bending, and since the residual stress is small due to the electron beam selective melting preparation technology, the acid treatment and zinc hydroxide solution treatment significantly increase the surface contact area, which is very beneficial for application in orthopedic repair and has broad application prospects.

[0039] In summary, compared with other traditional methods, the method of the present invention achieves synergistic improvement in the formability, porosity, mechanical properties and biocompatibility of the prepared porous thin-walled structure through titanium alloy powder selection, software modeling, printing parameter setting, scan line selection, stress relief annealing heat treatment, hot isostatic pressing, acid solution treatment and low-temperature treatment with zinc hydroxide aqueous solution; and the thickness, porosity, strength and other properties can be customized, with high resource utilization, short process and high efficiency. The product has a wide range of applicability in biomedical applications, which is conducive to large-scale industrial production and promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0041] Figure 1 Schematic diagram of a point scanning and jump strategy in a method for preparing a porous thin-walled structure by electron beam selective melting printing according to Example 1 of the present invention;

[0042] Figure 2 This is a physical picture of the thickness of a porous thin-walled sheet printed by a method for preparing a porous thin-walled structure by electron beam selective melting printing in Example 1 of the present invention, measured by a screw micrometer;

[0043] Figure 3 This is a physical image of a porous thin-walled sheet with large bending angles printed in a method for preparing a porous thin-walled structure by electron beam selective melting printing according to Example 1 of the present invention;

[0044] Figure 4 This is a physical image of a broken bone model used as a demonstration in a method for preparing a porous thin-walled structure by electron beam selective melting printing according to Example 1 of the present invention;

[0045] Figure 5 This is a physical image of a fractured bone model being covered and fixed with a printed porous thin-walled sheet, used as a demonstration in a method for preparing a porous thin-walled structure by electron beam selective melting printing in Example 1 of the present invention;

[0046] Figure 6 This is a scanning electron microscope image of a porous thin-walled sheet printed in a method for preparing a porous thin-walled structure by electron beam selective melting printing according to Example 2 of the present invention;

[0047] Figure 7 This is a porosity curve of a porous thin-walled sheet printed in a method for preparing a porous thin-walled structure by electron beam selective melting printing according to Example 2 of the present invention;

[0048] Figure 8 This is a photo of a tensile specimen of a porous thin-walled sheet printed in a method for preparing a porous thin-walled structure by electron beam selective melting printing according to Example 3 of the present invention;

[0049] Figure 9 This is a photo of a fractured sample of a porous thin-walled sheet printed in a method for preparing a porous thin-walled structure by electron beam selective melting printing according to Example 3 of the present invention after stretching;

[0050] Figure 10 This is a scanning electron microscope image of a porous thin-walled sheet printed in a method for preparing a porous thin-walled structure by electron beam selective melting printing in Example 4 of the present invention, showing the formation of fine titanium structures and zinc titanate nanostructures on the surface after solution treatment. DETAILED DESCRIPTION

[0051] The technical solution of the present invention is described below in conjunction with the accompanying drawings.

[0052] In the embodiments of the present invention, words such as "exemplarily" and "for example" are used to indicate examples, illustrations, or explanations. Any embodiment or design described as an "exemplary" in the present invention should not be interpreted as being preferred or advantageous over other embodiments or designs. Rather, the use of the word "exemplary" is intended to present concepts in a concrete manner. Furthermore, in the embodiments of the present invention, "and / or" can mean both or either of the two.

[0053] In the embodiments of the present invention, "image" and "picture" may sometimes be used interchangeably. It should be noted that, when the distinction between them is not emphasized, the meanings they convey are the same. "of," "corresponding," and "corresponding" may sometimes be used interchangeably. It should be noted that, when the distinction between them is not emphasized, the meanings they convey are the same.

[0054] In the embodiments of the present invention, sometimes a subscript such as W1 may be written as a non-subscript such as W1. When the difference is not emphasized, the meanings to be expressed are the same.

[0055] In order to make the technical problems, technical solutions and advantages to be solved by the present invention clearer, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0056] A method for preparing a porous thin-walled structure by electron beam selective melting printing, the method comprising the following steps:

[0057] S1. Raw material selection: According to the performance requirements of the porous thin-walled structure to be prepared, titanium alloy rotating electrode powder is selected to obtain raw titanium alloy powder or titanium aluminum alloy powder;

[0058] S2. Modeling: Using 3D modeling software to model the porous thin-walled structure according to its dimensions, a porous thin-walled model is obtained, and corresponding parameters are set for the molten pool width and the interval between the point-shaped molten pools in the porous thin-walled model;

[0059] S3. Printing parameter setting: The printing parameters need to be set within the density parameter range of the porous thin-walled structure to be prepared, so as to print a molten pool with a narrow width and high overlap efficiency;

[0060] S4, scan line selection and printing: When selecting the scan line, use the point melting and jump strategy; after the parameters are set and the scan line is selected, start printing the porous thin-walled structure;

[0061] S5. Cutting and stress relief annealing heat treatment: After printing, the porous thin-walled sample is cut from the base plate using a wire cutting method, sealed with a quartz tube and filled with argon gas, and then placed in a muffle furnace for stress relief annealing heat treatment, heating and cooling with the furnace;

[0062] S6. Hot isostatic pressing: The annealed sample is subjected to hot isostatic pressing to obtain a porous thin-walled sample with enhanced powder adsorption;

[0063] S7, acid solution treatment: treating the porous thin-walled sample with enhanced powder adsorption with an acid solution, and then performing ultrasonic cleaning to obtain a porous thin-walled sample with increased surface roughness;

[0064] S8. Treatment with zinc hydroxide aqueous solution: The porous thin-walled sample with increased surface roughness is treated with zinc hydroxide aqueous solution at low temperature, then treated at high temperature, and finally ultrasonically cleaned and dried to obtain a porous thin-walled final product with high biocompatibility and fine zinc titanate grown on the surface.

[0065] In particular, the particle size of the raw titanium alloy powder in S1 is 50-200 μm, and the types of titanium alloy include α-type titanium alloy and α+β dual-phase titanium alloy; the particle size of the raw titanium aluminum alloy powder is 50-150 μm, and the types of titanium aluminum alloy include 4822 alloy.

[0066] In particular, the 3D modeling software in S2 includes Solidworks or UG. The size range of the porous thin-walled model is 300-900μm. The porous part is obtained by the interval of the point-like melt pool. The melt pool width in the model is 150-300μm. The actual melt pool width is determined by the printing parameters and needs to be fed back and corrected based on the previous printing parameter range of the porous thin-walled structure to be prepared.

[0067] In particular, in S3, when the porous thin-walled structure component to be prepared is TC4, the printing parameters are set to a scanning speed of 1.5-3.0 m / s, a defocus value of 50, and a current of 60-120 mA; when the porous thin-walled structure component to be prepared is TA15, the printing parameters are set to a scanning speed of 1.0-2.5 m / s, a defocus value of 30, and a current of 70-130 mA; when the porous thin-walled structure component to be prepared is TC11, the printing parameters are set to a scanning speed of 1.0-2.5 m / s, a defocus value of 50, and a current of 80-150 mA; when the porous thin-walled structure component to be prepared is TA17, the printing parameters are set to a scanning speed of 1.2-2.8 m / s, a defocus value of 40, and a current of 90-160 mA.

[0068] In particular, the stress relief annealing heat treatment in S5 is heated at a temperature of 650-750°C, heated at a heating rate of 5-10°C / min, held at a temperature of 1-2h, and cooled at a cooling rate of 10-20°C / min.

[0069] In particular, the heating temperature of the hot isostatic pressing treatment in S6 is 850-1000° C., the gas pressure is 100-150 MPa, the gas medium is argon, and the holding time is 2-4 h.

[0070] In particular, the acid solution of the acid solution treatment in S7 is HF:HNO3:H2O in a ratio of 1:1:2, and the treatment time is 10-30 min; the frequency of ultrasonic cleaning is 20-40 Hz, and the power is 50-300 W; the thickness of the porous thin-walled sample with increased surface roughness is 100-500 μm, the porosity is 10-30%, the pore diameter is 50-200 μm, the surface roughness is Ra1-10 μm, the surface area is 200-1000 m² / m³, and the tensile strength is 100-400 MPa.

[0071] In particular, the low-temperature treatment of the zinc hydroxide aqueous solution in S8 is to place the porous thin-walled sample with increased surface roughness into a 0.1-0.5M zinc hydroxide aqueous solution for low-temperature treatment at 20-30°C for 1-2 hours; the high-temperature treatment is to subject the porous thin-walled sample with increased surface roughness after the low-temperature treatment with the zinc hydroxide aqueous solution to a high-temperature treatment at 80-90°C for 5-7 hours; the fine zinc titanate is in the form of flaky or columnar crystals with an average size of 1-10 μm.

[0072] Example 1

[0073] A preparation method for electron beam selective melting printing of 300 μm thick porous thin-walled TC4 alloy, the preparation method comprising the following steps:

[0074] S1. Raw material selection: According to the performance requirements of the porous thin-walled TC4 alloy to be prepared, TC4 alloy rotating electrode powder is selected, and the powder particle size is 50-100 μm, thereby obtaining raw titanium alloy powder;

[0075] S2. Modeling: Using the 3D modeling software Solidworks, a model was built based on the dimensions of the porous thin-walled TC4 alloy to be prepared. A 300 μm thick porous thin-walled model was obtained. The molten pool width and the interval between the point-shaped molten pools in the porous thin-walled model were set accordingly. The molten pool width was set to 280 μm, and the interval was set to 100 μm.

[0076] S3. Printing parameter setting: The printing parameters need to be set within the density parameter range of the porous thin-walled structure to be prepared, and the scanning speed should be 4 m / s, the defocus value should be 0, and the current should be 8.5 mA to print a molten pool with a narrow width and high overlap efficiency;

[0077] S4, scan line selection and printing: When selecting the scan line, use the point melting and jump strategy; after the parameters are set and the scan line is selected, start printing the porous thin-walled structure; the jump strategy is a short-line jump, and the jump strategy diagram is as follows Figure 1 As shown;

[0078] S5. Cutting and stress relief annealing heat treatment: After printing, the porous thin-walled sample is cut from the base plate using the wire cutting method. The specific physical figure is as follows: Figure 2 and Figure 3 As shown; a quartz tube is used to seal the tube and argon is filled into the tube, and then the tube is placed in a muffle furnace for stress relief annealing heat treatment. The heating temperature of the stress relief annealing heat treatment is 650°C, the heating rate of the furnace is 5°C / min, the holding time is 3h, and the cooling rate of the furnace is 5°C / min;

[0079] S6. Hot isostatic pressing: After annealing, the sample is subjected to hot isostatic pressing treatment with a heating temperature of 850°C, a gas pressure of 100 MPa, an argon medium, and a holding time of 2 h to obtain a porous thin-walled sample with enhanced powder adsorption;

[0080] S7. Acid solution treatment: The porous thin-walled sample with enhanced powder adsorption was treated with an acid solution having a ratio of HF:HNO3:H2O of 2:6:92 for 20 min. Ultrasonic cleaning was then performed at a frequency of 20 Hz and a power of 50 W to obtain a porous thin-walled sample with increased surface roughness. The porous thin-walled sample with increased surface roughness had a thickness of 300 μm, a porosity of 10%, a pore diameter of 50 μm, a surface roughness of Ra2, a surface area of ​​200 m² / m³, and a tensile strength of 150 MPa.

[0081] S8. Treatment with zinc hydroxide aqueous solution: The porous thin-walled sample with increased surface roughness is subjected to low-temperature treatment with zinc hydroxide aqueous solution, which is to place the porous thin-walled sample with increased surface roughness in 0.1M zinc hydroxide aqueous solution for low-temperature treatment at 20°C for 1 hour; then subjected to high-temperature treatment, which is to subject the porous thin-walled sample with increased surface roughness after low-temperature treatment with zinc hydroxide aqueous solution to high-temperature treatment at 80°C for 5 hours; finally, ultrasonic cleaning is performed and then drying is performed to obtain a final porous thin-walled product with high biocompatibility and fine zinc titanate grown on the surface.

[0082] The surface of the present embodiment is covered with a porous thin-walled product having high biocompatibility of fine zinc titanate. Figure 4 The broken bone shown in the figure has the following effect after wrapping: Figure 5 As shown in Figure 2, it can be seen that the porous thin-walled structure can effectively deform and fit into the fractured bone, thus playing a good fixation role.

[0083] In this embodiment, the fine zinc titanate is in the form of fine plate-like crystals with an average size of 3 μm.

[0084] Example 2

[0085] A method for preparing a porous thin-walled TC4 alloy with a thickness of 350-600 μm by electron beam selective melting printing, the preparation method comprising the following steps:

[0086] S1. Raw material selection: According to the performance requirements of the porous thin-walled TC4 alloy to be prepared, TC4 alloy rotating electrode powder is selected, and the powder particle size is 50-120 μm, thereby obtaining raw titanium alloy powder;

[0087] S2. Modeling: Using the 3D modeling software Solidworks, modeling was performed according to the dimensions of the porous thin-walled TC4 alloy to be prepared. Several porous thin-walled models with a thickness of 350-600 μm were obtained. The parameters for the molten pool width and the interval of the point-shaped molten pools in the porous thin-walled models were set accordingly. The molten pool width was set to 200 μm, and the interval was set to 80 μm.

[0088] S3. Printing parameter setting: The printing parameters need to be set within the density parameter range of the porous thin-walled structure to be prepared, with a scanning speed of 2.8 m / s, a defocus value of 0, and a current of 6.5 mA, so as to print a molten pool with a narrow width and high overlap efficiency;

[0089] S4, scan line selection and printing: When selecting the scan line, use the point melting and jump strategy; after the parameters are set and the scan line is selected, start printing the porous thin-walled structure; the jump strategy is a short-line jump, and the jump strategy diagram is as follows Figure 1 As shown;

[0090] S5. Cutting and stress relief annealing heat treatment: After printing, the porous thin-walled sample is cut from the base plate using the wire cutting method. The surface morphology and pore characteristics are as follows: Figure 6 As shown, the porosity is obtained by using the pressure pump test. Figure 7 As shown; a quartz tube is used to seal the tube and argon is filled into the tube, and then the tube is placed in a muffle furnace for stress relief annealing heat treatment. The heating temperature of the stress relief annealing heat treatment is 700°C, the heating rate of the furnace is 8°C / min, the holding time is 2h, and the cooling rate of the furnace is 8°C / min;

[0091] S6. Hot isostatic pressing: After annealing, the sample is subjected to hot isostatic pressing treatment at a heating temperature of 850°C, a gas pressure of 120 MPa, an argon medium, and a holding time of 2 h to obtain a porous thin-walled sample with enhanced powder adsorption;

[0092] S7. Acid solution treatment: The porous thin-walled sample with enhanced powder adsorption was treated with an acid solution having a ratio of HF:HNO3:H2O of 2:6:92 for 25 min. The sample was then ultrasonically cleaned at a frequency of 40 Hz and a power of 200 W to obtain a porous thin-walled sample with increased surface roughness. The porous thin-walled sample with increased surface roughness had a thickness of 400 μm, a porosity of 20%, a pore diameter of 100 μm, a surface roughness of Ra4, a surface area of ​​500 m² / m³, and a tensile strength of 500 MPa.

[0093] S8. Treatment with zinc hydroxide aqueous solution: The porous thin-walled sample with increased surface roughness is subjected to low-temperature treatment with zinc hydroxide aqueous solution, which is to place the porous thin-walled sample with increased surface roughness in 0.3M zinc hydroxide aqueous solution for low-temperature treatment at 30°C for 1 hour; then subjected to high-temperature treatment, which is to subject the porous thin-walled sample with increased surface roughness after low-temperature treatment with zinc hydroxide aqueous solution to high-temperature treatment at 90°C for 7 hours; finally, ultrasonic cleaning is performed and then drying is performed to obtain a final porous thin-walled product with high biocompatibility and fine zinc titanate grown on the surface.

[0094] In this embodiment, the fine zinc titanate is in the shape of fine flakes, and the average size is 6 μm.

[0095] Example 3

[0096] A preparation method for electron beam selective melting printing of 300 μm thick porous thin-walled TA15 alloy, the preparation method comprising the following steps:

[0097] S1. Raw material selection: According to the performance requirements of the porous thin-walled TA15 alloy to be prepared, TA15 alloy rotating electrode powder is selected, and the powder particle size is 50-100 μm, thereby obtaining raw titanium alloy powder;

[0098] S2. Modeling: Using the 3D modeling software Solidworks, a model was built based on the dimensions of the porous thin-walled TC4 alloy to be prepared. A 300 μm thick porous thin-walled model was obtained. The molten pool width and the interval between the point-shaped molten pools in the porous thin-walled model were set accordingly. The molten pool width was set to 200 μm, and the interval was set to 60 μm.

[0099] S3. Printing parameter setting: The printing parameters need to be set within the density parameter range of the porous thin-walled structure to be prepared, and the scanning speed should be 6 m / s, the defocus value should be 0, and the current should be 6 mA to print a molten pool with a narrow width and high overlap efficiency;

[0100] S4, scan line selection and printing: When selecting the scan line, use the point melting and jump strategy; after the parameters are set and the scan line is selected, start printing the porous thin-walled structure; the jump strategy is a short-line jump, and the jump strategy diagram is as follows Figure 1 As shown;

[0101] S5. Cutting and stress relief annealing heat treatment: After printing, the porous thin-walled sample is cut from the base plate using the wire cutting method. The specific physical figure is as follows: Figure 2 and Figure 3 As shown; a quartz tube is used to seal the tube and argon is filled into the tube, and then the tube is placed in a muffle furnace for stress relief annealing heat treatment. The heating temperature of the stress relief annealing heat treatment is 700°C, the heating rate of the furnace is 10°C / min, the holding time is 2h, and the cooling rate of the furnace is 10°C / min;

[0102] S6. Hot isostatic pressing: After annealing, the sample is subjected to hot isostatic pressing treatment at a heating temperature of 900°C, a gas pressure of 140 MPa, an argon medium, and a holding time of 3 h to obtain a porous thin-walled sample with enhanced powder adsorption;

[0103] S7. Acid solution treatment: The porous thin-walled sample with enhanced powder adsorption was treated with an acid solution having a ratio of HF:HNO3:H2O of 2:6:92 for 30 min. Ultrasonic cleaning was then performed at a frequency of 30 Hz and a power of 200 W. The porous thin-walled sample with increased surface roughness was obtained. The porous thin-walled sample with increased surface roughness had a thickness of 290 μm, a porosity of 20%, a pore diameter of 75 μm, a surface roughness of Ra6, a surface area of ​​700 m² / m³, and a tensile strength of 260 MPa.

[0104] S8. Treatment with zinc hydroxide aqueous solution: The porous thin-walled sample with increased surface roughness is subjected to low-temperature treatment with zinc hydroxide aqueous solution, which is to place the porous thin-walled sample with increased surface roughness in 0.2M zinc hydroxide aqueous solution for low-temperature treatment at 20°C for 1 hour; then subjected to high-temperature treatment, which is to subject the porous thin-walled sample with increased surface roughness after low-temperature treatment with zinc hydroxide aqueous solution to high-temperature treatment at 80°C for 5 hours; finally, ultrasonic cleaning is performed and then drying is performed to obtain a final porous thin-walled product with high biocompatibility and fine zinc titanate grown on the surface.

[0105] In this embodiment, the zinc titanate having a finer structure is formed. Figure 10 As shown, the fine zinc titanate is in the form of fine plate-like crystals with an average size of 5 μm.

[0106] Example 4

[0107] A method for preparing a 500 μm thick porous thin-walled TC4 alloy by electron beam selective melting printing, the preparation method comprising the following steps:

[0108] S1. Raw material selection: According to the performance requirements of the porous thin-walled TC4 alloy to be prepared, TC4 alloy rotating electrode powder is selected, and the powder particle size is 50-120 μm, thereby obtaining raw titanium alloy powder;

[0109] S2. Modeling: Using the 3D modeling software Solidworks, a model was built based on the dimensions of the porous thin-walled TC4 alloy to be prepared. A 500 μm thick porous thin-walled model was obtained. The parameters for the molten pool width and the interval between the point-shaped molten pools in the porous thin-walled model were set accordingly. The molten pool width was set to 300 μm, and the interval was set to 120 μm.

[0110] S3. Printing parameter setting: The printing parameters need to be set within the density parameter range of the porous thin-walled structure to be prepared, and the scanning speed should be 5 m / s, the defocus value should be 0, and the current should be 10 mA to print a molten pool with a narrow width and high overlap efficiency;

[0111] S4, scan line selection and printing: When selecting the scan line, use the point melting and jump strategy; after the parameters are set and the scan line is selected, start printing the porous thin-walled structure; among them, the jump strategy is short-line jump;

[0112] S5. Cutting and stress relief annealing heat treatment: After printing, the porous thin-walled sample was cut from the base plate using a wire cutting method. A quartz tube was used to seal the tube and argon was filled into the tube. The tube was then placed in a muffle furnace for stress relief annealing heat treatment. The heating temperature for stress relief annealing heat treatment was 750°C, the heating rate during furnace heating was 10°C / min, the holding time was 2h, and the cooling rate during furnace cooling was 10°C / min.

[0113] S6. Hot isostatic pressing: After annealing, the sample is subjected to hot isostatic pressing treatment at a heating temperature of 900°C, a gas pressure of 140 MPa, an argon medium, and a holding time of 2 h to obtain a porous thin-walled sample with enhanced powder adsorption;

[0114] S7. Acid solution treatment: The porous thin-walled sample with enhanced powder adsorption was treated with an acid solution having a ratio of HF:HNO3:H2O of 2:6:92 for 30 min. The sample was then ultrasonically cleaned at a frequency of 40 Hz and a power of 300 W to obtain a porous thin-walled sample with increased surface roughness. The porous thin-walled sample with increased surface roughness had a thickness of 500 μm, a porosity of 15%, a pore diameter of 60 μm, a surface roughness of Ra10, a surface area of ​​1000 m² / m³, and a tensile strength of 300 MPa.

[0115] S8. Treatment with zinc hydroxide aqueous solution: The porous thin-walled sample with increased surface roughness is subjected to low-temperature treatment with zinc hydroxide aqueous solution, which is to place the porous thin-walled sample with increased surface roughness in 0.3M zinc hydroxide aqueous solution for low-temperature treatment at 30°C for 1 hour; then subjected to high-temperature treatment, which is to subject the porous thin-walled sample with increased surface roughness after low-temperature treatment with zinc hydroxide aqueous solution to high-temperature treatment at 90°C for 7 hours; finally, ultrasonic cleaning is performed and then drying is performed to obtain a final porous thin-walled product with high biocompatibility and fine zinc titanate grown on the surface.

[0116] In this embodiment, the fine zinc titanate is in the shape of fine flakes, and the average size is 6 μm.

[0117] Example 5

[0118] A method for preparing a 200 μm thick porous thin-walled TC11 alloy by electron beam selective melting printing, the preparation method comprising the following steps:

[0119] S1. Raw material selection: According to the performance requirements of the porous thin-walled TC11 alloy to be prepared, TC11 alloy rotating electrode powder is selected, and the powder particle size is 50-120 μm, thereby obtaining raw titanium alloy powder;

[0120] S2. Modeling: Using the 3D modeling software Solidworks, a model was built based on the dimensions of the porous thin-walled TC11 alloy to be prepared. A 200 μm thick porous thin-walled model was obtained. The parameters for the molten pool width and the interval between the point-shaped molten pools in the porous thin-walled model were set accordingly. The molten pool width was set to 160 μm, and the interval was set to 100 μm.

[0121] S3. Printing parameter setting: The printing parameters need to be set within the density parameter range of the porous thin-walled structure to be prepared, and the scanning speed should be 1.5m / s, the defocus value should be 50, and the current should be 100mA to print a molten pool with a narrow width and high overlap efficiency;

[0122] S4, scan line selection and printing: When selecting the scan line, use the point melting and jump strategy; after the parameters are set and the scan line is selected, start printing the porous thin-walled structure; among them, the jump strategy is short-line jump;

[0123] S5. Cutting and stress relief annealing heat treatment: After printing, the porous thin-walled sample was cut from the base plate using a wire cutting method. A quartz tube was used to seal the tube and filled with argon gas. The tube was then placed in a muffle furnace for stress relief annealing heat treatment. The heating temperature for stress relief annealing heat treatment was 680°C, the heating rate during furnace heating was 6°C / min, the holding time was 2.5h, and the cooling rate during furnace cooling was 6°C / min.

[0124] S6. Hot isostatic pressing: After annealing, the sample is subjected to hot isostatic pressing treatment at a heating temperature of 900°C, a gas pressure of 140 MPa, an argon gas as the gas medium, and a holding time of 3.5 h.

[0125] S7. Acid solution treatment: The porous thin-walled sample with enhanced powder adsorption was treated with an acid solution having a ratio of HF:HNO3:H2O of 2:6:92 for 15 min. Ultrasonic cleaning was then performed at a frequency of 25 Hz and a power of 60 W. The resulting porous thin-walled sample had an increased surface roughness. The sample had a thickness of 190 μm, a porosity of 18%, a pore diameter of 80 μm, a surface roughness of Ra7, a surface area of ​​450 m² / m³, and a tensile strength of 180 MPa.

[0126] S8. Treatment with zinc hydroxide aqueous solution: The porous thin-walled sample with increased surface roughness is subjected to low-temperature treatment with zinc hydroxide aqueous solution, which is to place the porous thin-walled sample with increased surface roughness in 0.25M zinc hydroxide aqueous solution for low-temperature treatment at 30°C for 1.5 hours; then high-temperature treatment is performed, which is to subject the porous thin-walled sample with increased surface roughness after low-temperature treatment with zinc hydroxide aqueous solution to high-temperature treatment at 90°C for 5 hours; finally, ultrasonic cleaning is performed and then drying is performed to obtain a final porous thin-walled product with high biocompatibility and fine zinc titanate grown on the surface.

[0127] In this embodiment, the fine zinc titanate is in the shape of fine flakes, and the average size is 8 μm.

[0128] Example 6

[0129] A method for preparing a 420 μm thick porous thin-walled 4822 alloy by electron beam selective melting printing, the preparation method comprising the following steps:

[0130] S1. Raw material selection: According to the performance requirements of the porous thin-walled 4822 alloy to be prepared, TA17 alloy rotating electrode powder is selected with a powder particle size of 50-150 μm to obtain the raw material titanium aluminum alloy powder;

[0131] S2. Modeling: Using the 3D modeling software Solidworks, a model was built based on the dimensions of the porous thin-walled TA17 alloy to be prepared. A 420 μm thick porous thin-walled model was obtained. The molten pool width and the interval between the point-shaped molten pools in the porous thin-walled model were set accordingly. The molten pool width was set to 180 μm, and the interval was set to 150 μm.

[0132] S3. Printing parameter setting: The printing parameters need to be set within the density parameter range of the porous thin-walled structure to be prepared, and the scanning speed should be 2.6m / s, the defocus value should be 40, and the current should be 150mA to print a molten pool with a narrow width and high overlap efficiency;

[0133] S4, scan line selection and printing: When selecting the scan line, use the point melting and jump strategy; after the parameters are set and the scan line is selected, start printing the porous thin-walled structure; among them, the jump strategy is short-line jump;

[0134] S5. Cutting and stress relief annealing heat treatment: After printing, the porous thin-walled sample was cut from the base plate using a wire cutting method. A quartz tube was used to seal the tube and filled with argon gas. The tube was then placed in a muffle furnace for stress relief annealing heat treatment. The heating temperature for stress relief annealing heat treatment was 720°C, the heating rate during furnace heating was 8°C / min, the holding time was 2h, and the cooling rate during furnace cooling was 8°C / min.

[0135] S6. Hot isostatic pressing: After annealing, the sample is subjected to hot isostatic pressing treatment at a heating temperature of 900°C, a gas pressure of 120 MPa, an argon medium, and a holding time of 2.5 h to obtain a porous thin-walled sample with enhanced powder adsorption;

[0136] S7. Acid solution treatment: The powder adsorption-enhanced porous thin-walled sample was treated with an acid solution having a ratio of HF:HNO3:H2O of 2:6:92 for 20 min. Ultrasonic cleaning was then performed at a frequency of 30 Hz and a power of 300 W. The porous thin-walled sample with increased surface roughness was obtained. The porous thin-walled sample with increased surface roughness had a thickness of 410 μm, a porosity of 15%, a pore diameter of 80 μm, a surface roughness of Ra9, a surface area of ​​500 m² / m³, and a tensile strength of 300 MPa.

[0137] S8. Treatment with zinc hydroxide aqueous solution: The porous thin-walled sample with increased surface roughness is subjected to low-temperature treatment with zinc hydroxide aqueous solution, which is to place the porous thin-walled sample with increased surface roughness in 0.3M zinc hydroxide aqueous solution for low-temperature treatment at 25°C for 1 hour; then subjected to high-temperature treatment, which is to subject the porous thin-walled sample with increased surface roughness after low-temperature treatment with zinc hydroxide aqueous solution to high-temperature treatment at 85°C for 6 hours; finally, ultrasonic cleaning is performed and then drying is performed to obtain a final porous thin-walled product with high biocompatibility and fine zinc titanate grown on the surface.

[0138] In this embodiment, the fine zinc titanate is in the shape of fine flakes, and the average size is 8 μm.

[0139] The above scheme, the present invention proposes a method for preparing porous thin-walled structures by electron beam selective melting printing, which can solve the technical problems that in the existing technology, printing biomaterial titanium alloys can generally only prepare regular-shaped samples such as bulk porous materials, cylinders, femoral stems, bionic trabecular structure femoral head support rods, and the improvement of biocompatibility is through coatings, biological factor complexes, etc.

[0140] The porous thin-walled structure prepared by the present invention is extremely thin, with a minimum thickness of 300-400 μm, which is much lower than the porous structures in other existing technologies. It can provide high strength and plasticity while maintaining porosity, making it more widely applicable in biomedicine.

[0141] The porous thin-walled structure prepared by the present invention has excellent mechanical properties, with a porosity of up to 30%, a pore diameter of up to 200μm, a surface roughness of up to Ra1, a surface area of ​​up to 1000m² / m³, and a tensile strength of up to 400MPa. It can meet higher mechanical performance requirements as a bone fixation and repair material.

[0142] The porosity of the porous thin-walled structure prepared by the present invention can be controlled in the range of 10-30%, and different porosities can be controlled by adjusting the model and printing parameters.

[0143] The porous thin-wall structure prepared by the present invention can improve the surface roughness by at least 50% on the original basis through acid solution treatment and zinc hydroxide solution treatment.

[0144] In summary, compared with other traditional methods, the method of the present invention achieves synergistic improvement in the formability, porosity, mechanical properties and biocompatibility of the prepared porous thin-walled structure through titanium alloy powder selection, software modeling, printing parameter setting, scan line selection, stress relief annealing heat treatment, hot isostatic pressing, acid solution treatment and low-temperature treatment with zinc hydroxide aqueous solution; and the thickness, porosity, strength and other properties can be customized, with high resource utilization, short process and high efficiency. The product has a wide range of applicability in biomedical applications, which is conducive to large-scale industrial production and promotion.

[0145] It should be understood that the term "and / or" as used herein simply describes a relationship between associated objects, indicating that three possible relationships exist. For example, "A and / or B" can represent: A alone, A and B together, or B alone. A and B can be singular or plural. Furthermore, the character " / " as used herein generally indicates an "or" relationship between the associated objects, but it may also indicate an "and / or" relationship. For specific understanding, please refer to the context.

[0146] In this disclosure, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c" can mean: a, b, c, ab, ac, bc, or abc, where a, b, and c can be single or plural.

[0147] It should be understood that in various embodiments of the present invention, the size of the serial numbers of the above-mentioned processes does not mean the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.

[0148] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any modifications or substitutions that can be easily conceived by a person skilled in the art within the technical scope disclosed in the present invention should be included in the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be based on the scope of protection of the claims.

Claims

1. A method for preparing a porous thin-walled structure by electron beam selective melting printing, characterized in that: The method for preparing a porous thin-walled structure by electron beam selective melting printing is as follows: S1. Raw material selection: selecting titanium alloy rotating electrode powder according to the performance requirements of the porous thin-walled structure to be prepared, to obtain raw titanium alloy powder or raw titanium aluminum alloy powder; S2. Modeling: using 3D modeling software to model the porous thin-walled structure according to the size of the porous thin-walled structure to be prepared, obtaining a porous thin-walled model, and setting corresponding parameters for the molten pool width and the interval of the point-shaped molten pool in the porous thin-walled model; S3, printing parameter setting: The printing parameter setting needs to be selected within the dense parameter range of the porous thin-walled structure to be prepared, so as to print a molten pool with a narrow width and high overlap efficiency; S4, scan line selection and printing: when selecting scan lines, a point melting and jump strategy is used; After setting the parameters and selecting the scanning lines, start printing the porous thin-walled structure; S5. Cutting and stress relief annealing heat treatment: After printing is completed, the porous thin-walled sample is cut from the base plate using a wire cutting method, sealed with a quartz tube and filled with argon gas, and then placed in a muffle furnace for stress relief annealing heat treatment, heated and cooled with the furnace; S6. Hot isostatic pressing: The annealed samples are subjected to hot isostatic pressing to obtain porous thin-walled samples with enhanced powder adsorption; S7, acid solution treatment: treating the porous thin-walled sample with enhanced powder adsorption with an acid solution, and then performing ultrasonic cleaning to obtain a porous thin-walled sample with increased surface roughness; S8. Treatment with zinc hydroxide aqueous solution: The porous thin-walled sample with increased surface roughness is treated with zinc hydroxide aqueous solution at low temperature, then treated at high temperature, and finally ultrasonically cleaned and dried to obtain a porous thin-walled final product with high biocompatibility and fine zinc titanate grown on the surface.

2. The method for preparing a porous thin-walled structure by electron beam selective melting printing according to claim 1, characterized in that: The particle size of the raw titanium alloy powder in S1 is 50-200 μm, and the types of titanium alloy include α-type titanium alloy and α+β dual-phase titanium alloy; the particle size of the raw titanium aluminum alloy powder is 50-150 μm, and the types of titanium aluminum alloy include 4822 alloy.

3. The method for preparing a porous thin-walled structure by electron beam selective melting printing according to claim 1, characterized in that: The 3D modeling software in S2 includes Solidworks or UG. The size range of the porous thin-wall model is 300-900μm. The porous part is obtained by the interval of the point-shaped molten pool. The molten pool width in the model is 150-300μm. The actual molten pool width is determined by the printing parameters and needs to be corrected by feedback from the previous printing parameter range of the porous thin-walled structure to be prepared.

4. The method for preparing a porous thin-walled structure by electron beam selective melting printing according to claim 1, characterized in that: In S3, when the porous thin-walled structure component to be prepared is TC4, the printing parameters are set as scanning speed 1.5-3.0 m / s, defocus value 50, and current 60-120 mA; when the porous thin-walled structure component to be prepared is TA15, the printing parameters are set as scanning speed 1.0-2.5 m / s, defocus value 30, and current 70-130 mA; when the porous thin-walled structure component to be prepared is TC11, the printing parameters are set as scanning speed 1.0-2.5 m / s, defocus value 50, and current 80-150 mA; when the porous thin-walled structure component to be prepared is TA17, the printing parameters are set as scanning speed 1.2-2.8 m / s, defocus value 40, and current 90-160 mA.

5. The method for preparing a porous thin-walled structure by electron beam selective melting printing according to claim 1, characterized in that: The jump strategy in S4 is short-term jump.

6. The method for preparing a porous thin-walled structure by electron beam selective melting printing according to claim 1, characterized in that: The heating temperature of the stress relief annealing heat treatment in S5 is 650-750°C, the heating rate of the furnace heating is 5-10°C / min, the holding time is 1-2h, and the cooling rate of the furnace cooling is 10-20°C / min.

7. The method for preparing a porous thin-walled structure by electron beam selective melting printing according to claim 1, characterized in that: The heating temperature of hot isostatic pressing treatment in S6 is 850-1000°C, the gas pressure is 100-150MPa, the gas medium is argon, and the insulation time is 2-4h.

8. The method for preparing a porous thin-walled structure by electron beam selective melting printing according to claim 1, characterized in that: The acid solution of the acid solution treatment in S7 is HF:HNO3:H2O in a ratio of 1:1:2, and the treatment time is 10-30min; the frequency of ultrasonic cleaning is 20-40Hz, and the power is 50-300W; the thickness of the porous thin-walled sample with increased surface roughness is 100-500μm, the porosity is 10-30%, the pore diameter is 50-200μm, the surface roughness is Ra1-10μm, the surface area is 200-1000m² / m³, and the tensile strength is 100-400MPa.

9. The method for preparing a porous thin-walled structure by electron beam selective melting printing according to claim 1, characterized in that: The low-temperature treatment of zinc hydroxide aqueous solution in S8 is to place the porous thin-walled sample with increased surface roughness into 0.1-0.5M zinc hydroxide aqueous solution for low-temperature treatment at 20-30°C for 1-2h; the high-temperature treatment is to subject the porous thin-walled sample with increased surface roughness after low-temperature treatment with zinc hydroxide aqueous solution to high-temperature treatment at 80-90°C for 5-7h; the shape of the fine zinc titanate is flaky or columnar crystals with an average size of 1-10μm.

Citation Information

Patent Citations

  • Preparation method of porous titanium-alloy femoral head support rod in bionic bone trabecula structure

    CN104645419A

  • Functional bionic porous titanium alloy femoral head supporting rod and preparation method thereof

    CN112168431A

  • Method for additive manufacturing of porous material

    CN117548691A

  • Combined femoral stem for hip joint prosthesis and preparation method of combined femoral stem

    CN117883222A

  • Bone defect repair material capable of being customized individually and preparation method thereof

    CN118022054A

Cited By

  • Method for preparing TA15 titanium alloy thin-wall component through electron beam selective forming technology

    CN119952076A